1992
DOI: 10.1126/science.1553561
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Integrin VLA-2 as a Receptor for Echovirus 1

Abstract: Cell surface receptors for echovirus, a common human pathogen, were identified with monoclonal antibodies that protected susceptible cells from infection with echovirus 1. These monoclonal antibodies, which prevented virus attachment to specific receptor sites, recognized the alpha and beta subunits of the integrin VLA-2 (alpha 2 beta 1), a receptor for collagen and laminin. RD rhabdomyosarcoma cells expressed little VLA-2, did not bind to 35S-labeled virus, and resisted infection until transfected with comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
169
0
2

Year Published

1997
1997
2009
2009

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 288 publications
(178 citation statements)
references
References 31 publications
7
169
0
2
Order By: Relevance
“…When grown to A 595 ϭ 0.8, the cells (800 ml) were pelleted by centrifugation, washed with M9 minimal medium (12.8 g of Na 2 HPO 4 /liter, 3 g of KH 2 PO 4 /liter, 0.5 g of NaCl/ liter, 1 g of NH 4 Cl/liter, 1 mM MgCl 2 , 0.1 mM CaCl 2 , 0.5% glucose, 2 mg of thiamine/liter), and pelleted again. The pellet was resuspended in 500 ml of M9 minimal medium supplemented with 150 mg/liter of each of the following amino acids: threonine, phenylalanine, leucine, isoleucine, lysine, valine, and proline.…”
Section: Methodsmentioning
confidence: 99%
“…When grown to A 595 ϭ 0.8, the cells (800 ml) were pelleted by centrifugation, washed with M9 minimal medium (12.8 g of Na 2 HPO 4 /liter, 3 g of KH 2 PO 4 /liter, 0.5 g of NaCl/ liter, 1 g of NH 4 Cl/liter, 1 mM MgCl 2 , 0.1 mM CaCl 2 , 0.5% glucose, 2 mg of thiamine/liter), and pelleted again. The pellet was resuspended in 500 ml of M9 minimal medium supplemented with 150 mg/liter of each of the following amino acids: threonine, phenylalanine, leucine, isoleucine, lysine, valine, and proline.…”
Section: Methodsmentioning
confidence: 99%
“…However, the entry routes of SV40 and EV1 seem not to be identical (Marjomäki et al, 2002) and EV1 was found to be a unique tool to study the cell biology of caveolae. Importantly, EV1 uses ␣2␤1 integrin, a collagen receptor, to bind to cell surface (Bergelson et al, 1992) and therefore, the entry of EV1 can be used to study the role of integrins in caveolae function. Previous studies have shown that integrins can be coprecipitated with caveolin-1 (Wary et al, 1996(Wary et al, , 1998, suggesting that caveolae form a platform for integrin-mediated signaling.…”
Section: Introductionmentioning
confidence: 99%
“…contain the conserved arginine-glycine-aspartic acid Integrin-mediated cell entry is exploited by a number of (RGD) motif 9 and small peptides containing an RGD intracellular pathogens including adenovirus, 1,2 echodomain, particularly cyclic peptides, have high affinities virus, 3 foot-and-mouth disease virus 4 and the enterobacfor integrins. [10][11][12][13] Such peptides are easy to synthesise in terium Yersinia pseudotuberculosis.…”
Section: Introductionmentioning
confidence: 99%